Pre-operative fixed flexion deformity a curse to the knee arthroplasty surgeon? - Veeraraghavan, Raghav Ravi; Vanchi, Pravin Kumar; M., Mohan Kumar (International Journal of Research in Orthopaedics, 2018)
Background: The aim of the study was to study the effect of preoperative flexion deformity on the postoperative knee range of motion following total knee arthroplasty. Methods: A total of 28 knees were studied out of which twenty were osteoarthritis and eight were rheumatoid arthritis. Cruciate substituting and cruciate retaining implants were used. Patients above the age of 45 years with a minimum follow up period of two years from April 2010 were studied. Results: 28 knees had an average preoperative range of motion of 87.678. Patients with preoperative flexion deformity had postoperative range of motion of 97.5 degrees. The average postoperative flexion in 8 rheumatoid patients was 96.25 and 20 osteoarthritis patients was 107.462. Conclusions: The average postoperative range of motion was 105.538. Patients with a higher pre-operative range of motion had higher postoperative range of motion. Rheumatoid patients had a significantly low range of motion when compared to osteoarthritis patients. Patients with increased fixed flexion deformity had a significantly low postoperative range of motion.